Bilateral Comparison of the Three-dimensional Configuration in the Normal Ankle Syndesmosis: A non-Weightbearing and Weightbearing CT-analysis. Issue 4 (22nd October 2020) - Tsarukian, Greg; Peiffer, Matthias; Barg, Alexej; Huysse, Wouter; Sripanich, Yantarat; Van Oevelen, Aline C.; Buedts, Kristian; Audenaert, Emmanuel
Category: Ankle Introduction/Purpose: Syndesmotic ankle injuries can be present in up to one-fifth of all ankle trauma and may lead to syndesmotic instability or posttraumatic ankle osteoarthirtis on the long term. It remains challenging to distinguish syndesmotic ankle injuries from other types of ankle trauma. Currently, diagnosis is based on plain radiographs by comparing 2D measurements of the injured to the non-injured side. However, it is unclear to what extent the 3D configuration of the normal ankle syndesmosis is symmetrical during non- or weightbearing conditions. Therefore, our aim was two-fold (1) to establish reference values based on three-dimensional side-to-side comparison of the normal ankle syndesmosis imaged by a non-weightbearing (NWBCT) and weightbearing CT (WBCT) (2) to compare measurements obtained from a NWBCT with those of a WBCT. Methods: In this retrospective comparative cohort study, patients with a NWBCT (N=38; Mean age=51+-17.4 years) and WBCT (N=43; Mean age=48+-14.3 years) were analyzed. Inclusion criteria were a bilateral NWBCT or WBCT of the foot and ankle between January 2016 and December 2018. Exclusion criteria consisted of hindfoot pathology and an age <18 years or >75 years. CT images were segmented to obtain 3D models. Computer Aided Design (CAD) operations were used to mirror the left ankle and superimpose it over the right ankle (Fig. 1A). The apex of the lateral malleolus (AML), anterior tubercle (ATF) and posterior tubercle (PTF) were determined. The difference in the coordinates attached to these anatomical landmarks of the left distal fibula in the ankle syndesmosis with respect to the right were used to establish reference values within two standard deviations. The Mann-Whitney U-test was used to compare measurements from a NWBCT with a WBCT. Results: Reference values within two standard deviations are given for each 3D measurement derived from a NWBCT and WBCT-scan (Fig 1B). The highest difference in translation was detected in the anterior-posterior direction (Mean APNWBCT= 0.161mm; 2SD=3.212/ Mean APWBCT= -0.082mm; 2SD=2.374). The highest difference in rotation was detected in the external- internal direction (Mean EINWBCT= -0.484°; 2SD=8.720/ Mean EIWBCT= -0, 326°; 2SD=5.370). None of these differences were statistically significant in the normal ankle syndesmosis when obtained from a NWBCT scan compared to a WBCT scan (P>0.05). Conclusion: This study provides reference values of the three-dimensional configuration in the normal ankle syndesmosis based on side-to-side comparison. It did not demonstrate significant differences in the normal ankle syndesmosis between NWBT and WBCT scans. These novel 3D data contribute relevantly to previously established bilateral 2D radiographic reference values. In clinical practice, they will aid in distinguishing if a patient with a syndesmotic ankle lesion differs from normal variance in syndesmotic ankle symmetry.